Qualidade fisiológica e cinética de secagem em sementes de cumbaru (Dipteryx alata Vog.) - Vilarinho, Marcella Karoline Cardoso (2021)
Several factors contribute to the maintenance of seed quality in the production process, including drying, in addition, analyzing a seed, evaluating its physiological quality, constitutes an extremely important tool for maintaining the quality of the material. The objective of this work was to evaluate test methodologies to evaluate the physiological potential of cumbaru seeds, determine drying curves and adjust mathematical models to experimental data obtained in the drying of seeds, and verify, by means of x-ray images, the damage caused. by the drying process. For the quality evaluation tests, the imbibition curve test was performed, followed by the electrical conductivity, which had as procedures two two volumes of water, four quantities of seeds and ten times of imbibition. For accelerated aging, the test consisted of four exposure periods, and three preparations with and without saturated NaCl solution. Seeds were subjected to first count, germination, seedling emergence, shoot length, root length, shoot and root dry mass. Means were compared by Tukey test at 5% probability. In drying testicles, like cumbaru seeds were corrected by means of fruits collected from 20 matrices, approximately 255 days after anthesis. Seeds were extracted and stored for 15 days until they reached hygroscopic balance and water content of 14.5%. Drying was carried out in a continuous air flow dryer with an approximate temperature of 40 ° and a constant air flow of 2.5 m / s. The experimental data were fitted to twelve mathematical models and the values of the coefficients of determination (R2), the mean relative error (P) and the mean estimated error (SE) were used to verify the degree of adjustment of the models. After drying, 40 seeds from each treatment were submitted to x-ray test using the Faxitron MX-20 DC 12 equipment. The seeds dissipated root after 189 hours of water absorption. The electrical conductivity test shows good efficiency in the combination of 25 seeds in 100 ml of water, after 24 hours. The accelerated water aging test can be conducted at a temperature of 41°C combined with exposure over 48 hours. For drying, the Midilli mathematical model was the best fit to the experimental data. In the x-ray images, no cracks or any other damage generated by the drying process were observed.